The association between proton pump inhibitor use and risk of post-hospitalization acute kidney injury: a multicenter prospective matched cohort study - Yue Zhang; Nasrollah Ghahramani; Hadie Razjouyan; Djibril M. Ba; Vernon M. Chinchilli (BMC Nephrology, 2023)
Abstract Background Proton Pump Inhibitors (PPI) are among the most commonly used drugs to treat acid-related gastrointestinal disorders in the USA. Although PPI use has been linked to acute interstitial nephritis, the side effects of post-hospitalization acute kidney injury (AKI) and the progression of kidney disease still are controversial. We conducted a matched cohort study to examine the associations between PPI use and the side effects, especially in post-hospitalization AKI. Methods We investigated 340 participants from the multicenter, prospective, matched-cohort ASSESS-AKI study, which enrolled participants from December 2009 to February 2015. After the baseline index hospitalization, follow-up visits were conducted every six months, and included a collection of self-reported PPI use by participants. Post-hospitalization AKI was defined as the percentage increase from the nadir to peak inpatient SCr value was ≥ 50% and/or absolute increase ≥ 0.3 mg/dL in peak inpatient serum creatinine compared with baseline outpatient serum creatinine. We applied a zero-inflated negative binomial regression model to test the relationship between PPI use and post-hospitalization AKI. Stratified Cox proportional hazards regression models also were conducted to examine the association between PPI use and the risk of progression of kidney disease. Results After controlling for demographic variables, baseline co-morbidities and drug use histories, there was no statistically significant association between PPI use and risk of post-hospitalization AKI (risk ratio [RR], 0.91; 95% CI, 0.38 to 1.45). Stratified by AKI status at baseline, no significant relationships were confirmed between PPI use and the risk of recurrent AKI (RR, 0.85; 95% CI, 0.11 to 1.56) or incidence of AKI (RR, 1.01; 95% CI, 0.27 to 1.76). Similar non-significant results also were observed in the association between PPI use and the risk of progression of kidney diseases (Hazard Ratio [HR], 1.49; 95% CI, 0.51 to 4.36). Conclusion PPI use after the index hospitalization was not a significant risk factor for post-hospitalization AKI and progression of kidney diseases, regardless of the AKI status of participants at baseline.